MANAJEMEN BERBASIS NILAI-NILAI QUR’ANI DALAM MEMBANGUN ETIKA KINERJA BADAN EKSEKUTIF MAHASISWA : Manajemen Qur’ani - Salman Khanif, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Abstract Student organizations, particularly the Student Executive Board (Badan Eksekutif Mahasiswa/BEM), play a strategic role in developing students’ character, leadership, and managerial competencies. However, in practice, various issues related to work ethics are still commonly found, such as low discipline, lack of responsibility, weak coordination, and suboptimal transparency and organizational accountability. This study aims to analyze the implementation of management based on Qur’anic values within the Student Executive Board (BEM), examine the role of Qur’anic values in fostering the work ethics of organizational members, and identify their implications for improving the performance quality of student organizations. This research employs a descriptive qualitative approach using a library research method. Data were collected through a review of the Qur’an, Qur’anic exegesis (tafsir) literature, Islamic management books, scientific journals, and various relevant sources. Data analysis was conducted using content analysis techniques, while the validity of the findings was ensured through source triangulation. The results indicate that the implementation of management based on Qur’anic values is manifested through the internalization of the values of amanah (trustworthiness), shiddiq (truthfulness), tabligh (communicativeness), fathanah (wisdom and intelligence), musyawarah (shura/consultation), justice, and responsibility in organizational governance. These values contribute to the development of a professional, transparent, accountable, participatory, and integrity-based work culture. Furthermore, the application of Qur’anic values has positive implications for enhancing organizational work ethics through strengthening integrity, professionalism, work ethic, accountability, and the quality of student leadership. Keywords: Qur’anic Management, Work Ethics, Student Executive Board (BEM), Student Organizations, Islamic Values. Abstrak Organisasi kemahasiswaan, khususnya Badan Eksekutif Mahasiswa (BEM), memiliki peran strategis dalam mengembangkan karakter, kepemimpinan, dan kompetensi manajerial mahasiswa. Namun, dalam praktiknya masih ditemukan berbagai permasalahan etika kinerja, seperti rendahnya disiplin, kurangnya tanggung jawab, lemahnya koordinasi, serta belum optimalnya transparansi dan akuntabilitas organisasi. Penelitian ini bertujuan untuk menganalisis penerapan manajemen berbasis nilai-nilai Qur’ani dalam Badan Eksekutif Mahasiswa (BEM), mengkaji peran nilai-nilai Qur’ani dalam membangun etika kinerja pengurus, serta mengidentifikasi implikasinya terhadap peningkatan kualitas kinerja organisasi mahasiswa. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode studi kepustakaan (library research). Data diperoleh melalui telaah terhadap Al-Qur’an, kitab tafsir, buku manajemen Islam, jurnal ilmiah, dan berbagai literatur yang relevan. Analisis data dilakukan menggunakan teknik analisis isi (content analysis) dengan uji keabsahan melalui triangulasi sumber. Hasil penelitian menunjukkan bahwa penerapan manajemen berbasis nilai-nilai Qur’ani diwujudkan melalui internalisasi nilai amanah, shiddiq, tabligh, fathanah, musyawarah (syura), keadilan, dan tanggung jawab dalam tata kelola organisasi. Nilai-nilai tersebut berperan dalam membentuk budaya kerja yang profesional, transparan, akuntabel, partisipatif, dan berintegritas. Selain itu, penerapan nilai-nilai Qur’ani memberikan implikasi positif terhadap peningkatan etika kinerja organisasi melalui penguatan integritas, profesionalisme, etos kerja, akuntabilitas, serta kualitas kepemimpinan mahasiswa. Kata Kunci: Manajemen Qur’ani, Etika Kinerja, Badan Eksekutif Mahasiswa, Organisasi Kemahasiswaan, Nilai-Nilai Islam.